Etika dan Ajaran Moral Filsafat Islam: Pemikiran Para Filosof Muslim tentang Kebahagiaan - Mustain Mustain (Universitas Islam Negeri Mataram, 2013)
Muslim philosophers thought on ethics is not just about what is good and good action, but also at the same time order muslims to commit teachings of the good action. It means that the study of ethics does not stand alone but linked and fused with moral teachings. The end objective to be achieved with ethical and moral teachings is happiness that is described as the combination of elements of safety, peace, and quiet. According to Muslim philosophers, happiness can be achieved through acts of decency and deployment of deep sense of intellegence. They assume that the happiness achieved through the second way has higher levels of morality than through the first one. This is so, partly, since they find that such special achievement can only be achieved by special people, namely the philosophers.